Strategi Pemberdayaan Wirausaha Syariah Gen-Z Berbasis SWOT pada Start-Up Halal F&B di Indonesia: SWOT-Based Gen-Z Sharia Entrepreneurial Empowerment Strategy for Halal F&B Start-Ups in Indonesia - Aqbar, Khaerul; Azwar, Azwar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
This study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) faced by Gen-Z Muslimpreneurs and to formulate empowerment strategies aligned with the principles of Islamic entrepreneurship. The research employs a descriptive qualitative method using a literature review and documentation approach. The analysis is conducted through SWOT mapping, systematically structured based on findings from academic literature and official documents. The results reveal that Gen-Z Muslimpreneurs possess notable strengths, including religiosity, digital proficiency, and innovation capacity. However, they also encounter challenges such as limited managerial experience and restricted access to capital. Externally, they benefit from the growing halal market and supportive regulatory frameworks, yet they must also navigate a highly competitive industry and complex certification processes. Based on this mapping, four strategic directions are proposed: (1) digital Islamic business training (SO), (2) collaboration with halal business incubators (WO), (3) trend filtration based on Islamic values (ST), and (4) mentoring and regulatory literacy (WT). These strategies are further developed into the Operational Framework for Empowering Gen-Z Muslimpreneurs, comprising four core pillars: integrated training, business collaboration, halal trend laboratories, and legal mentoring for business transformation. The findings are expected to serve as both conceptual and practical references for communities, training institutions, and policymakers in fostering a sustainable and competitive Islamic entrepreneurship ecosystem in the era of the global halal industry.